AUDIT QUALITY, INDEPENDENT COMMISSIONER, RETURN ON ASSETS, AND FACTORS AFFECTED OF EARNINGS MANAGEMENT - Leona Vierman Alzura; Indra Arifin Djashan (E-Jurnal Akuntansi TSM, 2023)
This research objectives are to obtain empirical evidence about factors that affect earnings management, specifically, the influence of leverage, firm size, return on asset, sales growth, audit quality, independent commissioner, institutional ownership, and managerial ownership on earnings management. The population that is used in this research are all non-financial companies listed in the Indonesia Stock Exchange from 2019 to 2021 and apply purposive sampling as the sampling method. With this method, it is obtained that one hundred nineteen (119) non-financial companies fit with the sampling criteria and selected as the sample with the total of 357 data. This research uses multiple regression methods to analyze the data. The result obtained from multiple regression shows that return on asset, audit quality, and independent commissioner have an effect on earnings management. On the contrary, other independent variables, which are leverage, firm size, sales growth, board of director, institutional ownership, and managerial ownership have no effect on earnings management.